Assessment of Serum Urea and Creatinine Levels in Diabetic Patients - Ullah, Wahid; Nazir, Azhar; Israr, Hasnain; Hussain, Shahid; Farooq, Muhammad (BioScientific Review, 2023)
Diabetic nephropathy is the leading cause of renal morbidity which occurs when chronic diabetes destroys the filtering system of the kidneys. Serum urea and creatinine are widely used as renal function test parameters. This study aims to assess the level of serum urea and creatinine in diabetic patients and their relationship with each other. The study was conducted in Ayub Teaching Hospital from September 15 to December 20, 2019. A total of 176 samples from confirmed diabetic patients were analyzed including 85 female and 91 male patients. Also, 83 control samples were taken for this study. Serum urea and creatinine levels were assessed to evaluate diabetic nephropathy in diabetic patients. SPSS (version 23) was used for statistical analysis. Pearson correlation analysis was used to check the relationship of blood sugar level, creatinine, and urea. Descriptive statistics (mean ± SD) were measured for the continuous variable. Scatter plot diagrams were added for the easy visualization and interpretation of the data. The significant level was set at p < 0.05. Out of the 176 diabetic samples, 32 had abnormally high serum creatinine and 66 had abnormal serum urea. In controls, one individual had high creatinine and three individuals had high serum urea. A significant increase in both urea and creatinine levels was observed in diabetic samples. Both serum urea and creatinine showed a strong positive correlation with the level of glucose and remained statistically significant (p < 0.01). Similarly, blood glucose level showed a strong correlation with the renal function test parameters. Hence, it was concluded that serum urea and creatinine are important parameters to assess kidney function in diabetes mellitus.